art and affection in school inclusion: potency and non-representative thinking - Barreiro, Mateus Freitas [UNESP]; Carvalho, Alonso Bezerra [UNESP]; Furlan, Marta Regina (State Univ Rio De Janeiro, 2018)
This article has as main objective to investigate art and the affection as options of will to power in the school inclusive process, having as theoretical reference, mainly, the thoughts of Deleuze and Guattari. The discussion begins in the conceptual formation of the notion affect (affection) and its other conceptual components that involve the will to power and the no representative thought. It is now necessary to include a new version of the register of a representative logic that encodes the subject's experience and reduces his/her affective power. In this perspective, the art as aesthetic experience is a way of amplifying power, once they are affected, they are empowered to a differentiated perspective in the means of conceiving and living life. The methodology is theoretical, with reflections on the affections in their relation with the deficient still to come? in the school, in its articulation with art and the aesthetic experience, and it involves the recognition of the social, psychological inequalities, among others. In this sense, art extends the affections, not only in the subjects under consideration, which possess a cultural background, but the appreciation depends on a sensible perception more than on a representative thinking.
Keywords: art; affection; school inclusion; deleuze